Educating for mobile computing: addressing the new challenges - Burd, B. (2013)
Computers that once filled rooms now fit in our pockets, and unlike their predecessors, mobile computers abound. The mobile industry is surging, with more smartphones being sold to consumers than PCs [17]. But does the rise of mobility impact computer science education? We claim that computer science educators must seriously consider mobility as they examine their curriculum. In this working group report, we offer a brief defense of why mobile computing belongs in our courses, summarize our survey of several hundred courses which already incorporate it, and discuss how educators might adopt it in their own courses. We hope that this work will help computer science educators make informed decisions about incorporating mobile computing into their courses and provide examples of such integration on different levels, ranging from individual projects or lecture topics to mobile computing as a learning context for an entire course.